The Effect of Company Size, Solvency, and Public Accounting Firm Size on Audit Delay - Indah Kusumawati (Perkumpulan Praktisi Akuntansi Indonesia, 2022)
This study aims to examine and analyze the effect of company size, solvency, and public accounting firm size on audit delay in agricultural companies listed on the IDX from 2017-2019 as partially and simultaneously. This research uses quantitative research using the purposive sampling method. The analysis method in this research study used descriptive statistics, classic assumption tests, hypothesis testing which consisted of simple and multiple linear regression with a significance level of 5%. This research was conducted by selecting research data according to the sample criteria of 15 agricultural companies based on established criteria. The type of data used secondary data obtained from IDX and the company's official website. The results of this research show for the partial test such as company size and public accounting firm size does not affect audit delay, but for solvency affects the audit delay. The result simultaneously tests for company size, solvency, and public accounting firm size tests do not affect audit delay.